Heart-type fatty acid-binding protein (H-FABP) as an early diagnostic biomarker in patients with acute chest pain - Vupputuri, Anjith (Indian Heart J, 2015)
BACKGROUND: Heart-type fatty acid-binding protein (H-FABP) is an emerging biomarker, which was found to be sensitive for the early diagnosis of acute myocardial infarction (AMI). We prospectively investigated the usefulness of H-FABP determination for the evaluation of acute chest pain in patients arriving at the emergency department. METHODS: Fifty-four patients presenting with acute ischemic chest pain were evaluated. H-FABP was estimated at admission using latex-enhanced immunoturbidimetric assay. Serial cardiac troponin I (cTnI), creatinine kinase-MB (CK-MB) determination, ischemia workup with stress testing, and/or coronary angiogram (CAG) were performed according to standard protocols. RESULTS: The sensitivity and specificity of H-FABP was 89.7% and 68%, for cTnI it was 62.1% and 100%, and for CK-MB it was 44.8% and 92%, respectively for diagnosis of AMI. The sensitivity of H-FABP was found to be far superior to initial cTnI and CK-MB, for those seen within 6 h (100% vs. 46.1%, 33% respectively). On further evaluation of patients with positive H-FABP and negative cTnI, 71.4% of the patients had significant lesion on CAG, indicating ischemic cause of H-FABP elevation. Six patients with normal cTnI and CK-MB with high H-FABP had ST elevation on subsequent ECGs and were taken for primary angioplasty. CONCLUSION: H-FABP is a highly sensitive biomarker for the early diagnosis of AMI. H-FABP as early marker and cTnI as late marker would be the ideal combination to cover the complete diagnostic window for AMI. Detection of myocardial injury by H-FABP may also be applied in patients with unstable angina. H-FABP can also be used as a marker for early detection of STEMI before the ECG changes become apparent.